Association of Visceral Adipose Tissue With Hypertension: Results From the NHANES 2011–2018 and Mendelian Randomization Analyses - Jia Liao; Miaohan Qiu; Jing Li; Yi Li; Yaling Han (The Journal of Clinical Hypertension)
ABSTRACT The causal relationship between visceral adipose tissue (VAT) and hypertension remains unclear. We aimed to examine the potential association between them using observational and two‐sample Mendelian randomization (MR) analyses. Data from the National Health and Nutrition Examination Survey (NHANES) 2011–2018 were used, applying multivariable logistic regression analysis to investigate the association between VAT mass and hypertension risk. Independent genetic variants related to VAT mass were derived from genome‐wide association studies (GWAS) in 325 153 UK Biobank participants. The primary analysis employed the random‐effects inverse‐variance weighted (IVW) method, with MR‐Egger, weighted median, simple mode, and weighted mode as sensitivity analyses. A total of 7661 participants were included. After adjusting for confounding factors, increased VAT mass was associated with a higher risk of hypertension (quartile 4 vs. quartile 1: OR:1.85, 95% confidence intervals [CI]: 1.31–2.63). Furthermore, VAT mass exhibited greater accuracy than body mass index (BMI) in predicting hypertension (areas under the curve [AUC]: 0.701 vs. 0.676, p for comparison < 0.001). The MR analyses demonstrated a causal relationship between increased VAT mass and the risk of hypertension in primary analyses (odds ratio [OR]:1.768, 95% CI: 1.594–1.861). Consistent findings across various MR models substantiate the robustness and strength of this causal relationship. These analyses provide additional support for both the positive association and causal relationship between elevated VAT and the risk of developing hypertension, suggesting that targeted interventions for VAT may be beneficial in preventing hypertension.